Cardiogenic Shock Due to Late Chimney Stent Failure Following Valve-in-Valve Transcatheter Aortic Valve Replacement - Daniel Nour, MBBS (JACC: Case Reports, 2019)
Although the safety of valve-in-valve transcatheter aortic valve replacement has improved, coronary ostium obstruction remains a significant complication, with chimney stenting a possible solution to circumvent this complication. In this case, we discuss the failure of a chimney stent in a case of valve-in-valve transcatheter aortic valve replacement resulting in cardiogenic shock. (Level of Difficulty: Advanced.)